2021
DOI: 10.1097/md.0000000000028098
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the sublingual gland developing lung metastasis 20 years after primary treatment

Abstract: Rationale: Adenoid cystic carcinoma (ACC) is a rare malignant tumor that primarily occurs in the salivary glands. Distant metastases can develop despite favorable local control. Moreover, distant metastasis of ACC can occur after a long time interval without local recurrence. We report the first case of ACC of the sublingual gland that developed lung metastasis 20 years after primary treatment. Patient concerns: A 52-year-old man was referred to our department with a 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…The risk factors for lung metastasis include tumor size, perineural invasion and local recurrence [2]. Lung metastasis in ACC is usually asymptomatic for a long time and a size more than 2.5 centimetres has been identified as a risk factor for metastasis [2,9]. In the present case, the clinical presentation was similar to that reported in literature except lack of paresthesia [2,8,9].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The risk factors for lung metastasis include tumor size, perineural invasion and local recurrence [2]. Lung metastasis in ACC is usually asymptomatic for a long time and a size more than 2.5 centimetres has been identified as a risk factor for metastasis [2,9]. In the present case, the clinical presentation was similar to that reported in literature except lack of paresthesia [2,8,9].…”
Section: Discussionsupporting
confidence: 79%
“…The slow but constant growth, numerous local recurrences, and hematogenous dissemination, primarily to the lung, liver, bone, and brain, are characteristics of ACC's natural history [8]. The risk factors for lung metastasis include tumor size, perineural invasion and local recurrence [2]. Lung metastasis in ACC is usually asymptomatic for a long time and a size more than 2.5 centimetres has been identified as a risk factor for metastasis [2,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at ACC-specific post-PM survival outcomes, the results are heterogenous. There are multiple single-patient case reports of PM for ACC reporting varied clinical benefit, with differences in survival largely dictated by the development of subsequent distinct lung lesions or new metastases at non-pulmonary sites [ 130 , 131 , 132 , 133 ]. We identified 10 studies which included multiple ACC patients undergoing PM and reported ACC-specific survival data (as compared to the 12 reports above that presented aggregate outcomes across histologies).…”
Section: Local Therapy For Oligometastatic Lung Diseasementioning
confidence: 99%
“…Lung is the most common site of distant metastasis of ACC derived from the head and neck, followed by bone, liver, and brain (4,5). In even rarer cases, ACC may arise from the submucosal tracheobronchial glands in the pulmonary system, and this accounts for a mere 0.04-0.2% of all primary lung tumors (6)(7)(8). It is difficult to distinguish between primary ACC of the lung (PACCL) and metastatic ACC of the lung (ACCL), as both conditions manifest atypical respiratory obstructive symptoms, including cough, chest pain, and dyspnea (2,9,10).…”
Section: Introductionmentioning
confidence: 99%